Adolescent Light Cigarette Smoking Patterns and Adult Cigarette Smoking. (27th June 2016) - Wiener, R. Constance; Shockey, Alcinda K. Trickett; Morgan, Susan K.
Abstract : Purpose. Light cigarette smoking has had limited research. The purpose of this study was to examine the relationship between light smoking in adolescence with smoking in adulthood. Methods. National Longitudinal Study of Adolescent Health data, Waves I and IV, were analyzed. Previous month adolescent smoking of 1–5 cigarettes/day (cpd) (light smoking); 6–16 cpd (average smoking); 17 or more cpd (heavy smoking); and nonsmoking were compared with the outcome of adult smoking. Results. At baseline, 15.9% of adolescents were light smokers, 6.8% were average smokers, and 3.6% were heavy smokers. The smoking patterns were significantly related to adult smoking. In logistic regression analyses, adolescent light smokers had an adjusted odds ratio (AOR) of 2.45 (95% CI: 2.00, 3.00) of adult smoking; adolescent average or heavy smokers had AOR of 5.57 (95% CI: 4.17, 7.43) and 5.23 (95% CI: 3.29, 8.31), respectively. Conclusion. Individuals who initiate light cigarette smoking during adolescence are more likely to smoke as young adults. Practical Implications. When screening for tobacco use by adolescents, there is a need to verify that the adolescents understand that light smoking constitutes smoking. There is a need for healthcare providers to initiate interventions for adolescent light smoking.